(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2024)
Shape analysis of a large sample of the thecideid brachiopod Thecidellina from the Pliocene and Pleistocene rocks on the Caribbean island of Curaçao highlights asymmetry within the population. However, the 30 analysed specimens display a lack of a consistent asymmetry. The brachiopods were cemented to substrates by a cicatrix, accommodated by a change in shell structure. The plastic morphology of Thecidellina may have been due to overcrowding and competition for resources on limited substrates.